Culture and emotional economy of migration - Badrī Nārāyaṇa (Routledge, 2019)
This book studies how the act of migration is a motivating constituent in the production of popular culture in both the homeland and the destination. It looks at the formations of cultures in the process of identity-making of approximately 200 million Indians scattered across the world, from colonial to contemporary times. The volume is an in-depth exploration of the flow of cultures and their interactions through a study of north Indian migrants who underwent two waves of emigration – from the Bhojpuri region to the Dutch colony of Suriname between 1873 and 1916 to work on sugar, coffee, cotton and cocoa plantations, and their descendants who moved to The Netherlands following the Surinamese independence in 1975. It compares this complex network of cultures among the migrants to the folk culture of the Bhojpuri region from where large-scale migration is still taking place. The work draws on archival records, secondary literature, folk songs, rare photographs, and extensive fieldwork across continents – the Bhojpuri region, Mumbai, Surat and Ghaziabad in India, and Suriname and The Netherlands.